1996
DOI: 10.1021/jm9508651
|View full text |Cite
|
Sign up to set email alerts
|

Tyrosine Kinase Inhibitors. 10. Isomeric 4-[(3-Bromophenyl)amino]pyrido[d]- pyrimidines Are Potent ATP Binding Site Inhibitors of the Tyrosine Kinase Function of the Epidermal Growth Factor Receptor

Abstract: Following the discovery of the very high inhibitory ability of the 4-[(3-bromophenyl)amino]-quinazolines against the tyrosine kinase activity of the epidermal growth factor receptor (EGFR) (e.g., 3, IC50 0.029 nM), four series of related pyrido[d]pyrimidines bearing electron-donating groups at the 6- or 7-positions have been synthesized and evaluated. The compounds were prepared by nucleophilic substitution of the corresponding 6- and 7-fluoro analogues. While members of all series showed potent inhibitory act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
118
0
2

Year Published

1997
1997
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(123 citation statements)
references
References 34 publications
3
118
0
2
Order By: Relevance
“…1a, 2a and 3a). This is consistent with other reports (32,(36)(37)(38)(39). We also found that EGF treatments inhibited the DU145 prostate cell line in vitro (Figs.…”
Section: Discussionsupporting
confidence: 94%
“…1a, 2a and 3a). This is consistent with other reports (32,(36)(37)(38)(39). We also found that EGF treatments inhibited the DU145 prostate cell line in vitro (Figs.…”
Section: Discussionsupporting
confidence: 94%
“…To further understand the relationship between the EGFR and c-Src, the KM12 cell lines were pre-treated with a drug that speci®cally blocks EGFR activation (PD 158780) (Rewcastle et al, 1996) and then treated with 100 ng/ml EGF for 10 min prior to analysis of whole cell lysates by phosphotyrosine Western blots (Figure 7). EGF stimulation of untreated cells predictably enhanced autophosphorylation of protein bands consistent with EGFR (170 kDa) and c-Src (60 kDa) in the highly-metastatic cell lines (KM12 SM, KM12 L4A) but had no apparent e ect on c-Src in the poorly-metastatic cell line (KM12 C), mirroring previous experiments (see Figure 2a).…”
Section: Speci®c Inhibitors Of Egfr Block Ligand Activation Of Egf Anmentioning
confidence: 99%
“…Previous studies have demonstrated the requirement of ROS for the mitogenic response [1,7,10,18]. To examine whether H # O # …”
Section: Lpa-stimulated Dna Synthesis Is Partially Inhibited By Catalasementioning
confidence: 99%
“…To assess whether EGF receptor tyrosine kinase also mediates LPA-stimulated H # O # release, cells were treated with PD158780, a tyrosine kinase inhibitor specific for the EGF receptor [17][18][19], and LPA-or EGF-stimulated H # O # release was measured. As shown in Figure 3b, EGF stimulated H # O # release in HaCaT cells.…”
Section: Figure 4 Inhibition Of Lpa-and Egf-stimulated Tyrosine Phospmentioning
confidence: 99%
See 1 more Smart Citation